2011
DOI: 10.1111/j.1469-8986.2011.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Different mental rotation strategies reflected in the rotation related negativity

Abstract: In a mental rotation task of objects, typically, reaction time (RT) increases and the rotation related negativity (RRN) increases in amplitude with increasing angles of rotation. However, in a mental rotation task of hands, different RT profiles can be observed for outward and inward rotated hands. In the present study, we examined the neurophysiological correlates of these asymmetries in the RT profiles. We used a mental rotation task with stimuli of left and right hands. In line with previous studies, the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
63
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 59 publications
(106 reference statements)
12
63
0
1
Order By: Relevance
“…Instead, Parsons [10] found that participants took longer to correctly judge hand laterality when they were presented with laterally compared to medially rotated pictures of hands. Since then, this finding has been repeatedly replicated [10-16]. This consistent observation was taken as evidence that participants internally simulate a movement of the hand - thus, engage in MI - to solve the task.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Instead, Parsons [10] found that participants took longer to correctly judge hand laterality when they were presented with laterally compared to medially rotated pictures of hands. Since then, this finding has been repeatedly replicated [10-16]. This consistent observation was taken as evidence that participants internally simulate a movement of the hand - thus, engage in MI - to solve the task.…”
Section: Introductionmentioning
confidence: 69%
“…Thus, the P300 becomes less positive as the mentally rotated angle increases. A number of variables have been found to influence RRN amplitude during the HLJ task [14,16]. First, the RRN is more marked for palm view compared to back view pictures of hands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategy selection pertaining to spatial reasoning has been extensively studied in the mental rotation literature (Hegarty, 2010;Khooshabeh, Hegarty, & Shipley, 2013;Kozhevnikov, Hegarty, & Mayer, 2002;Meneghetti, Cardillo, Mammarella, Caviola, & Borella, 2016;Shepard & Metzler, 1971;Ter Horst, Jongsma, Janssen, van Lier, & Steenbergen, 2012). For several decades' researchers investigating strategy selection during spatial thinking tasks have attempted to operationalize the strategies that participants' use, but an inconsistent vocabulary has been employed.…”
Section: Strategy Selection Versus Flexibility: Using Eye-trackers Tomentioning
confidence: 99%
“…medial-over-lateral advantage (MOLA; Funk & Brugger, 2008), MR is faster for rotations toward the midsagittal plane (medial rotations) and longer for rotations away from that plane (lateral rotations; Coslett, Medina, Kliot, & Burkey, 2010;Funk & Brugger, 2008;Gawryszewski, Silvados-Santos, Santos-Silva, Lameira, & Pereira, 2007;Parsons, 1994;ter Horst, Jongsma, Janssen, van Lier, & Steenbergen, 2012). These findings suggest that subjects internally simulate the movement of their own body part in order to match the position of the stimulus (Parsons, 1994;Sirigu & Duhamel, 2001) by adopting motor imagery in first-person perspective (for a review, see Corradi-Dell'Acqua & Tessari, 2010) and thus rendering the imagery sensitive to anatomical constraints (Fourkas, Ionta, & Aglioti, 2006).…”
mentioning
confidence: 99%